2021
DOI: 10.22456/1679-9216.111672
|View full text |Cite
|
Sign up to set email alerts
|

Mammary Fibroepithelial Hyperplasia in a Male Cat

Abstract: Background: Feline mammary hyperplasia (FMH) is a benign disease that commonly affects young females, once it is caused by the exaggerated stimulation of endogenous or exogenous progestogen. FMH leads to acute edema and inflammation of the mammary glands and frequently evolve to ulcerations, secondary infections, and systemic clinical signs. Even though it is rare in male cats, progesterone therapy or an unknown endogenous source of hormone can cause the disease. This report aims to describe a case of FMH in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 9 publications
(18 reference statements)
0
0
0
Order By: Relevance
“…In queens with fibroepithelial mammary hyperplasia, increases in tissue volume lead to perfusion problems, erythema, pain, ulceration, dark and necrotic areas on the mammary gland skin (Bonatto et al, 2021;Voorwald et al, 2021), as well as systemic effects such as high fever, tachycardia, anorexia, and sepsis are also observed (Loretti et al, 2004;Voorwald et al, 2021). In this case, growth was observed to cover all mammary lobes, similar to other researchers (Baştan et al, 2004;Vitasek & Dendisova, 2006;Küçükbekir et al, 2020), and there were no local and general symptoms except hyperemia in some mammary lobes.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…In queens with fibroepithelial mammary hyperplasia, increases in tissue volume lead to perfusion problems, erythema, pain, ulceration, dark and necrotic areas on the mammary gland skin (Bonatto et al, 2021;Voorwald et al, 2021), as well as systemic effects such as high fever, tachycardia, anorexia, and sepsis are also observed (Loretti et al, 2004;Voorwald et al, 2021). In this case, growth was observed to cover all mammary lobes, similar to other researchers (Baştan et al, 2004;Vitasek & Dendisova, 2006;Küçükbekir et al, 2020), and there were no local and general symptoms except hyperemia in some mammary lobes.…”
Section: Discussionsupporting
confidence: 83%
“…However, as waiting for this process can result in several adversities in the mammary glands, this process should be accelerated by early intervention (Allen, 1973;Görlinger et al, 2002). Although fibroepithelial hyperplasia is generally seen in young queens (Baştan et al, 2004;Uçmak et al, 2011), cases can also be observed in male and female cats of all ages who are administered exogenous synthetic progestins for a short or long time (Görlinger et al, 2002;Nak et al, 2004;Bonatto et al, 2021). Similar to the report of Görlinger et al, (2002), a case of MFH was encountered in a queen at a very early age without any treatment, therefore, estrogen and progesterone hormones of individual mammary glands were encountered, suggesting that MFH may have occurred as a result of increased susceptibility due to factors such as genetics and age.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation